Narrative Functions in Batu Karang Seribu Folktale - Amalia, Resti; Bowo, Tri Arie; Lubis, Donal Fernado (Berumpun: International Journal of Social, Politics, and Humanities, 2024)
The aim of the study is to analyze Batu Karang Seribu using theory from Vladimir Propp. Batu Karang Seribu is one of the tourist destinations particularly in Kundi village West Bangka Regency hence it is important to study the folktales surrounding it to enhance the site’s popularity. This study applies descriptive qualitative research method using a content analysis approach. This study employs certain characteristics of Propp’s narrative model and applied them in the folklore which aim at finding the morphological reading of the narrative functions. The data were gathered and identified according to the forms of narrative functions. All the categorized contents were analyzed based on the narrative functions and symbols. Based on the analysis, there are 11 functions found in the story. There were the function of Absentation (β1), Delivery (ζ), Reconnaissance (ε), Trickery (η3), Complicity (θ1), Villainy (A14), Meditation (B4), provision of a magical agent (F6), Guidance (G4), struggle (H), and Transfiguration (T). In short, the function is as follows: β1ζεη3θ1A14B4F6G4HT. The function of Struggle (H) and Transfiguration (T) is unusual since the villain is not the one who have combat with the hero but a new character, Pahit Lidah. He defeats the hero by transforming him into a stone.